Injury incidence and prevalence in Finnish top-level football – one-season prospective cohort study. Issue 2 (3rd April 2022) - Kurittu, Einari; Vasankari, Tommi; Brinck, Tuomas; Parkkari, Jari; Heinonen, Olli J.; Kannus, Pekka; Hänninen, Timo; Köhler, Klaus; Leppänen, Mari
ABSTRACT: Ojective: To investigate the injury characteristics in Finnish male football players. Design: One-season prospective epidemiological study. Data were collected via injury reports from the medical staff and directly from the players using the Olso Sports Trauma Research Center Health Questionnaire. Participants: The first team squads of Finnish football league (n = 12 teams, 236 players). Main outcome measurement: Injury incidence. Results: A total of 541 injuries occurred during the exposure of 62 878 hours. Injury incidence per 1000 exposure hours was 8.6 (30.6 in matches and 3.4 in training). A player sustained on average 2.3 (median 2, range 0–13) injuries during the study. Thigh and ankle were the most commonly injured body parts for acute injuries and hip/groin were the most commonly injured body part for overuse injuries. The median absence time for all injuries was 12 (range 0–107) days, 12 (range 0–107) for acute, and 8 (range 0–61) for overuse injuries. Thigh injuries caused the greatest consequences in terms of absence from full participation (median 5 days, range 0–88). Conclusion: Lower limb muscle injuries were the most prevalent injuries in the study. Collecting data directly from the players enabled to report more injuries compared to what was reported only by the medical staff.